STRATEGI KEPEMIMPINAN DALAM PENDIDIKAN - Baharuddin (Jurnal Riset Guru Indonesia, 2022)
The purpose of this article is to provide a general view of the concept of leadership from several aspects, namely psychology, management and education through presenting various ideas and interpretations, although not final conclusions. The main discussion in this article: "What ideas about leadership concepts in the scientific literature on psychology, management and education. Articles are written with descriptive studies with the results that the leadership strategy is closely related to managerial skills so that a person's capacity to implement conceptual skills related to humans and technical leadership skills to carry out management functions.